STRATEGI MANAJEMEN SDM BERBASIS ANALISIS SWOT DALAM MENINGKATKAN KINERJA KARYAWAN PADA CV CENDANA - Nonda Elyzza Umar; Erna Nur Faizah; Rudi Wibowo; Abdul Majid (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze human resource management (HRM) strategies based on SWOT analysis in improving employee performance at CV Cendana, an LPG distribution company. A qualitative approach was used with interviews and direct observation methods to explore the strengths, weaknesses, opportunities, and threats that affect the effectiveness of HR strategies. The results showed that employee loyalty, harmonious work culture, and flexible organizational structure are the company's main strengths. However, there are still weaknesses such as the absence of a structured training system and undocumented performance evaluations. External opportunities in the form of advances in digital training technology and government support can be utilized to improve training and HR development strategies. Through the mapping of SO, WO, ST, and WT strategies, this research provides applicable strategic recommendations for companies in building adaptive, competitive, and sustainable HR policies.